Harmony of Positive Character Through Extracurricular Teenage Scientific Groups Based On Al-Ghazali’s Perspective - Widyasari, Erna; Fauziati, Endang; Maryadi, Maryadi; Haryanto, Sigit (International Journal of Education, Information Technology, and Others, 2024)
Character education has become crucial in individual development, especially in today's modern era. This article explains an effective approach to character formation through extracurricular, teenage scientific groups, by integrating Al-Ghazali perspectives. The main focus is on Al-Ghazali's views of ethics, morality, and positive moral development. The extracurricular scientific groups of adolescents have the potential to achieve character education goals. By defining the purpose of the group, its relationship with the character, and the methods of development used, this article analyzes the compatibility of Al-Ghazali values with the activity of the teenage scientific group. Case studies highlight the implementation of this concept, evaluate the positive impact on group members, and highlight the role of guidance. Challenges and opportunities in integrating traditional concepts into modern contexts were also discussed. In conclusion, this article provides an in-depth insight into how extracurricular teenage scientific groups can be an effective medium in shaping characters according to Al-Ghazali's views.